Kemauan Bertindak dalam Resusitasi Jantung Paru pada Siswa Sekolah Menengah Atas - Eka Yulia Fitri Y; Dhona Andhini; Zulian Effendi; Santri Handayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify high school students' willingness to provide essential life support to victims of cardiac arrest outside the hospital. The research method used in this study is a descriptive survey. The results showed that more students reported a willingness to perform CPR to friends (89.58%), closest family members (81.25%), and relatives (77.08%) than other victims. The two main reasons respondents did not want to do CPR were fear of endangering the victim (68.75%) and fear of legal problems (43.75%). As many as 89.29% of female respondents and 90% of male respondents want to do CPR. In conclusion, respondents are willing to act in CPR on OHCA and wish to learn about it. The positive attitude shown by respondents can be a driving force for creating education and training strategies that can increase knowledge, skills, and willingness to act on CPR among high school students. Keywords: Cardiac arrest, Willingness to Act, Cardiopulmonary Resuscitation